ChemInform Abstract: Synthesis of Oxacyclic Scaffolds via Dual Ruthenium Hydride/Broensted Acid‐Catalyzed Isomerization/Cyclization of Allylic Ethers. Issue 36 (9th September 2014) - Ascic, Erhad; Ohm, Ragnhild G.; Petersen, Rico; Hansen, Mette R.; Hansen, Casper L.; Madsen, Daniel; Tanner, David; Nielsen, Thomas E.
Abstract A variety of tetrahydropyranoindoles and related scaffolds are synthesized from allylic ethers via an isomerization/oxocarbenium cyclization sequence.